Studi Literatur Perbandingan Komunikasi dan Hubungan Masyarakat: Transformasi Era Awal Digital Hingga Sekarang (1990 – 2024) - Nasution, Khofifah Mulya; Hidayat, Taufik Wal (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study examines the comparison of communication and public relations in the early digital era, covering the period from 1990 to 2024. Using a literature study approach, this study analyzes the significant changes that have occurred in communication methods and public relations practices along with the development of information technology. In the early 1990s, communication was dominated by conventional media, which limited interaction between organizations and the public. However, with the advent of the internet and social media, organizations are starting to shift to more interactive and responsive methods of communication. The study found that digital transformation is not only changing the way information is delivered but also creating new opportunities to build stronger relationships with audiences. The results of the analysis show that public relations practices have evolved into a more dynamic strategy, with an emphasis on engagement and transparency. In this context, this study offers insights into the comparison of communication and public relations in the transformation of the early digital era to the present. These findings are expected to contribute to the development of more effective communication strategies in the future.